2012
DOI: 10.1111/jsap.12008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a pre‐tied ligating loop for liver biopsy and liver lobectomy

Abstract: The pre-tied ligating loop is a versatile and safe method for liver biopsy or lobectomy. As with other surgical techniques, alternative methods of haemostasis should always be available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Similar PCV decreases of 1% to 3% have been previously reported in studies 21,22 of liver lobectomy in dogs and cats and laparoscopic hepatic biopsy in dogs. Similar PCV decreases of 1% to 3% have been previously reported in studies 21,22 of liver lobectomy in dogs and cats and laparoscopic hepatic biopsy in dogs.…”
Section: Discussionsupporting
confidence: 87%
“…Similar PCV decreases of 1% to 3% have been previously reported in studies 21,22 of liver lobectomy in dogs and cats and laparoscopic hepatic biopsy in dogs. Similar PCV decreases of 1% to 3% have been previously reported in studies 21,22 of liver lobectomy in dogs and cats and laparoscopic hepatic biopsy in dogs.…”
Section: Discussionsupporting
confidence: 87%
“…Achieving an effective airway seal is essential when lung lobectomy is performed; adequate hemostasis of the pulmonary artery and vein is similarly important, but this was not evaluated in our cadaveric study. The effectiveness of a PLL for hemostasis is, however, supported by several previous in vivo studies that provided evidence for its clinical use for complete and partial liver lobectomies in dogs and cats 8,10,11 and for gastrointestinal and urogenital applications in man. 4,5 From our clinical experience, we estimate that the pulmonary vessels in dogs are of similar size compared to the hepatic lobar vessels, and, thus, effective occlusion of these vessels was anticipated to be possible with this technique.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 Their simple construction makes PLL a cost effective option because they are less expensive than a linear stapling device. Pre-tied ligature loops have been described for complete or partial liver lobectomies in dogs and cats [8][9][10][11] and for lung biopsy in dogs. 12 In dogs, the PLL has been evaluated as a safe method of tissue biopsy up to 3 cm from the lung lobe margin in a canine cadaver model.…”
Section: Introductionmentioning
confidence: 99%
“…RELAVE et al (2008) reported that biopsies collected in equine lungs had a complication rate of 31%, including slippage of the loop ligature or bleeding from the pulmonary parenchyma. Although, the successful use of a pre-tied ligating loop for resection of tissue for diagnosis or treatment has been reported in various clinical scenarios in humans, horses, dogs and cats (PONSKy & ROTHENBERG 2008;CUDDy et al 2013;DA CONCEIÇÃO et al 2018;CRONIN et al 2019). In the present study, we not observed slippage or bleeding from the pulmonary parenchyma after pre-tied loop ligature applied and biopsy collected.…”
Section: Discussionmentioning
confidence: 99%